DIE INDUSTRIEENTWICKLUNG UND DAS ORGANISIEREN DES STÄDTISCHEN RAUMES IM RUMÄNISCHEN SEKTOR DER UNTEREN DONAU. DER STUDIENFALL: GALAŢI - RADU SĂGEATĂ; MIRCEA BUZA (Revue Roumaine de Géographie)
Industrial development and urban space organisation in the Romanian sector of the Danube. Case study: Galaţi City. The Danube in Romania represents an axis of discontinuity between natural regions, each with its own distinct traits: the Carpathian Mountains, the Romanian Plain, Moldavian and the Bessarabian Plateaus in the north, the Pre-Balkan Plateau in the south and the Dobruja Plateau in the east. As a result, the limitrophe zone of the Danube in Romania, mostly cross-border, shows particular social and economic characteristics. Although the River Danube has favoured the development of an urban area, yet this area does not form a coherent system; the limitrophe zone itself is extremely rural. Under communism, the impetuous industrialisation drive, with highlight on the iron-and-steel industry, ship-building and chemistry, had alienated the urban ecosystems from the availabilities of their limitrophe zones, a situation that has enhanced the economic and social difficulties of the ongoing restructuring process. Within this context, the development of Galaţi City under communism was subordinated to political decision-making, therefore the location of a big iron-and-steel plant there had disturbing effects both for the City (by fast population growth due to the influx of migrants, concomitantly with the westwards extension of the built-in area) and for the rural neighbourhood (by diverging fluxes of materials and energy). The development of the City has been hampered by several restrictive factors, primarily by the downsagging of the terrain in its constructed area. All these changes have resulted in the development of some more economic and social favourable areas, which have attracted investments, and of others, less favourable ones, that have been declining.